On the radar frequency dependence of polar mesosphere summer echoes. Issue 6 (16th November 2020) - Ge, ShuCan; Li, HaiLong; Meng, Lin; Wang, MaoYan; Xu, Tong; Ullah, Safi; Rauf, Abdur; Hannachid, Abdel
Abstract : Polar mesosphere summer echoes (PMSEs) are very strong radar echoes in the polar mesopause in local summer. Here we present the frequency dependence of the volume reflectivity and the effect of energetic particle precipitation on modulated PMSEs by using PMSEs observations carried out by European Incoherent SCATter (EISCAT) heating equipment simultaneously with very high frequency (VHF) radar and ultra high frequency (UHF) radar on 12 July 2007. According to the experimental observations, the PMSEs occurrence rate at VHF was much higher than that at UHF, and the altitude of the PMSEs maximum observed at VHF was higher than that at UHF. Overlapping regions were observed by VHF radar between high energetic particle precipitation and the PMSEs. In addition, high‐frequency heating had a very limited impact on PMSEs when the UHF electron density was enhanced because of energetic particle precipitation. In addition, an updated qualitative method was used to study the relationship between volume reflectivity and frequency. The volume reflectivity was found to be inversely proportional to the fourth power of radar frequency. The theoretical and experimental results provide a definitive data foundation for further analysis and investigation of the physical mechanism of PMSEs.